Transcervical resection of myoma (TCRM): Part II - Peng-Hui Wang; Szu-Ting Yang; Wen-Hsun Chang; Hung-Hsien Liu; Wen-Ling Lee (Taiwanese Journal of Obstetrics & Gynecology)
In the part I, we have already reported the rationale, efficacy, complication, and limitation of using transcervical resection of myoma (TCRM) in the management of women with symptomatic uterine fibroids, particularly for those belonging to the International Federation of Gynaecology & Obstetrics (FIGO) myoma classification system as FIGO types 0–2. The current review as part II, the discussion will focus on the techniques, tips and complication prevention or management when TCRM is applied in the management of women with symptomatic submucosal myoma. With better understanding for TCRM-related basic knowledge, such as rationale, efficacy, complication, technique review, tips and prevention or management of complications, plus the well-training and carefully performing TCRM through preceding accurate diagnosis, and good and careful preparation and intensive monitoring during operation and using effective strategy to preventing short-term and long-term complications, TCRM can become one of most powerful strategies in offering the less traumatic injury to the uterus, and an effective and safe surgical approach in dealing with women with symptomatic submucosal myoma.